Trend Beragama Kaum Gen-Z Dan Relevansinya Terhadap Moral - Rohmatul Fajriyah, Atina; Puspita Sari, Fransisca; Salsabilla, Rasya; Naufal Muslich Ginting, Muhammad; Noor Herdiansyah, Rizky; Muhammad Noor, Aditia (Postmodernism: Indonesian Journal of Multidisciplinary Islamic Studies, 2025)
Generation Z (gen-z) is a term from researchers to mean a group of people who live after the Millennial Generation, namely humans who were born in the digital era or technological advances. This causes the characteristics of the Gen-Z to be different from the previous generation. One of the most striking differences between Generation Z and other generations is the religious trend of Generation Z. At this time the pattern of consumption of information about religion has undergone a significant change, namely changing to more practical digital and online-based media. Technological advances in this digital era not only have a positive impact on generation Z, they also have a negative impact. Therefore, moral education is needed for generation Z. The importance of moral education is intended to overcome things such as misunderstandings in accepting religious knowledge, and so on. Moral education is also needed so that Generation Z understands how to position themselves well, and how they must act and behave in every condition. The current problem of Generation Z is their moral and mental weakness, they sometimes feel the most right and feel the most wronged when they are being advised, even though it is all for their own good.